EFEKTIVITAS SISTEM CASH ON DELIVERY PADA E-COMMERCE LAZADA SELAMA MASA PANDEMI COVID-19 - Adryan Garda Yogatama; Mochamad Nurhadi; Larasati Ayu Sekarsari; Immanuel Candra Irawan (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to measure how effective the cash on delivery system is based on several variables, namely consumer perceptions, service quality and customer satisfaction. The object under study is the cash on delivery payment system on one of the e-commerce applications, namely Lazada. This research uses quantitative research methods. Data collection was carried out by using the survey method. The method used in sampling is non-probability sampling with purposive sampling technique. The sample of this study were 159 Lazada users in Indonesia who had used the cash on delivery payment system in the last 3 months. The research uses quantitative methods with multiple linear regression analysis techniques assisted by SPSS software. The result of this study is that consumer perceptions and customer satisfaction have a positive and significant influence on purchase intentions, meaning that consumer perceptions are effective for presenting purchase intentions on the Lazada application through the cash on delivery system. However, service quality has a negative and insignificant effect, which means that the service quality of the cash on delivery system at Lazada is not yet effective in influencing consumer purchase intentions. However, consumer perceptions, customer satisfaction and service quality simultaneously influence purchase intentions with the cash on delivery system at Lazada.